Distance to pig farms as risk factor for community-onset livestock-associated MRSA CC398 infection in persons without known contact to pig farms—A nationwide study - Anker, J. C. H. (Zoonoses Public Health, 2018)
MRSA CC398 is an emerging MRSA strain found in livestock, mainly in pigs. Direct occupational livestock contact is the principal risk factor for human MRSA CC398 infection. Nonetheless, in recent years, an increasing number of MRSA CC398 cases has been observed in persons without known pig contact. Such cases, referred to as MRSA CC398 of unknown origin (MUO CC398), have, like livestock-onset (LO) MRSA CC398 cases, been found concentrated in rural, livestock-producing areas. The presence of MUO CC398 cases indicates alternative and unknown MRSA CC398 transmission pathways into the community. We performed a nationwide study in Denmark of the geographic distributions of MRSA cases in general and persons with MUO CC398 or LO MRSA CC398 infections (1 January 2006–11 February 2015), with the Danish population as background population. Place of living of study persons was mapped using the ArcGIS software, and information on pig farms was retrieved from the Central Husbandry Register. The incidence of MUO CC398 infections was clearly higher in rural than in urban areas, and such cases lived on average closer to pig farms than the general population. However, within three pig-farming-dense municipalities, patients with MUO CC398 infections did not live closer to pig farms than population controls. This shows that direct environmental spread from neighbouring pig farms of MRSA CC398 is unlikely. Instead, community spread through other means of transmission than direct spread from farms may more likely explain the clustering of MUO CC398 in livestock-dense areas.